Physical activity and sleep on the risk of overweight among Grade 5 students in Gampaha Medical Office of Health area, Sri Lanka - Upuli Perera; Chrishantha Abeysena (College of Community Physicians of Sri Lanka, 2017)
Background: Overweight in childhood is an emerging health problem in developing countries. The increasing trend in overweight is associated with three important factors; dietary habits, physical activity and socio-economic changes. Objective: To determine the risk factors for overweight among Grade 5 students in schools of Gampaha Medical Officer of Health area. Methods: A case control study was carried out. Cases were defined as Grade 5 students who were overweight, which was identified based on the age and sex specific body mass index (BMI) centile charts recommended by the International Obesity Task Force. Controls were those who were not overweight selected from the same class of cases. A pre-tested self-administered questionnaire was administered to the parent or guardian of the children to assess the physical activities, dietary pattern and socio-demographic characteristics of children. Multiple logistic regression analysis was applied. Risk factors for overweight were assessed using adjusted odds ratio (aOR) with 95% confidence interval (CI). Results: Less physical activity during free times at home (OR=1.86; 95% CI=1.01, 3.42), less physical activity during weekends (OR=2.06; 95% CI=1.18, 3.61), less overall physical activity (OR=1.77; 95% CI=1.08, 2.9) and sleeping more than 8 hours per day (OR=0.46; 95% CI=0.29, 0.74) showed statistically significant associations with overweight in bivariate analysis. Of them, after adjusting for confounders, engaging in less physical activities during the weekend was a risk factor (aOR=2.17; 95% CI=1.22, 3.86) for overweight. Sleeping more than 8 hours per day was a protective factor (aOR=0.46; 95% CI=0.29, 0.74) for overweight. Other characteristics of physical activities, socio-demographic factors, high-fibre diet and fatty food did not show any significant association with overweight. Conclusions: Less physical activity especially during weekends showed a two-fold risk for overweight while sleeping more than 8 hours per day showed a similar protective effect for overweight among Grade 5 school children.